MafB, a new Maf family transcription activator that can associate with Maf and Fos but not with Jun. - Kataoka, K (1994)
We have identified a new member of the maf oncogene family and named it mafB. This gene is expressed in a wide variety of tissues and encodes a protein of 311 amino acids containing a typical bZip motif in its carboxy-terminal region. In the bZip domain, MafB shares extensive homology not only with v-Maf but also with other Maf-related proteins. As expected from its structure, MafB forms a homodimer through its leucine repeat structure and specifically binds Maf-recognition elements (MAREs). In addition, MafB forms heterodimers with v-Maf and Fos through its zipper structure. However, unlike v-Maf, MafB fails to associate with Jun. Transient cotransfection assays revealed that both v-Maf and MafB act as transactivators for a promoter linked to MAREs, although MafB is less potent than v-Maf. As is the case for the c-maf gene, overexpression of the mafB gene induces transformation of chicken embryo fibroblasts in vitro. Through formation of numerous bZip dimers, the Maf family proteins along with the AP-1 components should provide great diversity in transcriptional regulation for a wide variety of genes.